Radial Artery Tonometry to Monitor Blood Pressure and Hemodynamics in Ambulatory Left Ventricular Assist Device Patients in Comparison With Doppler Ultrasound and Transthoracic Echocardiography: A Pilot Study. Issue 3 (11th October 2018) - Zayat, Rashad; Drosos, Vasileios; Schnoering, Heike; Lee, Ju‐Yeon; Bleilevens, Christian; Musetti, Giulia; Jansen‐Park, So‐Hyun; Kang, HeeJung; Menon, Ares K.; Schmitz‐Rode, Thomas; Autschbach, Rüdiger; Hatam, Nima; et al.
Abstract: Noninvasive measurements of blood pressure (BP) and cardiac output (CO) are crucial in the follow‐up of continuous‐flow left ventricular assist device (CF‐LVAD) patients. For our pilot study, we sought to compare BP measurements between a tonometry blood pressure pulse analyzer (BPPA) (DMP‐Life, DAEYOMEDI Co., Ltd., Gyeonggi‐do, South Korea) and Doppler ultrasound in CF‐LVAD patients, as well as to compare the BPPA estimated CO to LVAD calculated blood flow and to the patient's intrinsic CO estimated with transthoracic echocardiography (TTE). Ambulatory CF‐LVAD patients (6 HeartMate, 26 HeartMate II), were included. According to TTE findings, patients were then subdivided in two groups: patients with an opening aortic valve (OAV) [ n  = 21] and those with an intermittent opening aortic valve (IOAV) [ n  = 11]. We found a very good correlation of systolic BP (SBP) measurements between the two methods, BPPA and Doppler ultrasound ( r  = 0.87, P  < 0.0001). Bland‐Altman plots for SBP revealed a low bias of −4.6 mm Hg and SD of ±4.7 mm Hg. In CF‐LVAD patients with IOAV, the BPPA‐CO had a good correlation with the LVAD‐flow ( r  = 0.78, P  < 0.0001), but in OAV patients, there was no correlation. After adding the patient's intrinsic CO, estimated from TTE in patients with OAV to the LVAD‐flow, we found a very good correlation between the BPPA‐CO and LVAD‐flow + TTE‐CO ( r  = 0.81, P  = 0.002). Our study demonstrated that compared with the standard clinical method, Doppler ultrasound, the BPPA measured BP noninvasively with good accuracy and precision of agreement. In addition, tonometry BPPA provided further valuable information regarding the CF‐LVAD patient's intrinsic CO.